Odslužen les - surovinski vir z velikim potencialom - Humar, Miha (Gozdarski vestnik, 2016)
Wood is the most important renewable material in Slovenia. Its low carbon footprint is one of the most important environmental benefits of the wood. However, low environmental profile is valid only for wood which is managed properly at the end of its service life. Deposition of wood and other biodegradable materials to landfills results in huge methane emissions, which completely diminish environmental benefits of wood, if methane is not somehow captured. Therefore, proper management systems for recovered wood at the end of its service life have to be developed.
Keywords: les; wood; odslužen les; recovered wood; cascade use of wood; kaskadna raba lesa; odpadki; waste